2001
DOI: 10.1099/0022-1317-82-6-1465
|View full text |Cite
|
Sign up to set email alerts
|

Defining CAR as a cellular receptor for the avian adenovirus CELO using a genetic analysis of the two viral fibre proteins

Abstract: The coxsackievirus and adenovirus receptor (CAR) is a high affinity receptor used by adenoviruses, including adenovirus type 5 (Ad5). The adenovirus fibre molecule bears the high affinity cell binding domain of Ad5, allowing virions to attach to CAR. The avian adenovirus CELO displays two fibre molecules on its capsid and it was logical to expect that the cell binding functions of CELO might also reside in one or both of these fibres. We had previously shown that the cell binding properties of CELO resemble Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 38 publications
(50 reference statements)
1
55
0
Order By: Relevance
“…[16][17][18][19] Avian Ad CELO (FAV-1) seems to be a promising candidate for the development of alternative Ad vectors that are able to transfer genes into different human cells, with the efficiencies comparable to those of Ad5 vectors. [17][18][19][20] There are three features of the CELO virus that distinguish it from human Ads and provide additional advantages for gene therapy applications. First, there is no pre-existing immune response to this virus in human population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Avian Ad CELO (FAV-1) seems to be a promising candidate for the development of alternative Ad vectors that are able to transfer genes into different human cells, with the efficiencies comparable to those of Ad5 vectors. [17][18][19][20] There are three features of the CELO virus that distinguish it from human Ads and provide additional advantages for gene therapy applications. First, there is no pre-existing immune response to this virus in human population.…”
mentioning
confidence: 99%
“…Indeed, unlike other Ads, the CELO virus is characterized by two different-length fibers at each vertex of a virion. 20 The CELO long fiber is responsible for the recognition of the coxsackie-Ad receptor (CAR), [20][21][22][23][24] and, unlike the short CELO fiber, it is dispensable for both virus assembly and its penetration into permissive cells. 20 Thus, it seems that the directed modifications within the long fiber can alter virus specificity to definite cell types without significant change of its natural tropism.…”
mentioning
confidence: 99%
“…However, while Coxsackie-adenovirus receptor (CAR) is the primary receptor for initial cell attachment for most human adenovirus serotypes, 1 it has also been demonstrated to act as a CELO virus fibre 1 receptor, permitting attachment to cells lacking the avian cell surface receptor. 38 Following staining with an antihCAR antibody, flow cytometry revealed that high levels of surface CAR expression in DU-145 and PNT-2 cells ( Figure 2, Table 1) correlated with greater CELOluc transduction ( Figure 1) and likewise low CAR expression on PC-3 and PNT1a cells correlated with poor levels of CELOluc transduction.…”
Section: Immunocytochemical Analysis Of Human Car Expression On Prostmentioning
confidence: 96%
“…4,5 To avoid pre-existing humoral immunity in patients, several groups have investigated adenovirus serotypes from alternative species such as cows, [6][7][8][9][10][11][12][13][14] sheep, [15][16][17][18][19][20][21][22][23][24][25] chimpanzees, [26][27][28] dogs [29][30][31][32][33][34][35][36] and chickens. [37][38][39][40] Chicken embryo lethal orphan virus (CELO; fowl adenovirus type 1), characterized as an infectious agent in 1957, 41 is attractive as a gene delivery vector since it is simple and cheap to produce in bulk in chicken embryos and has a good safety profile being completely replication defective in human cells, even in the presence of wild-type human adenovirus. 42 CELO is structurally similar to mammalian adenoviruses possessing an icosahedral capsid of 70-80 nm composed of hexon and penton proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation